(untitled) - Noori, Hamid (New Yersey, 1990)
Book provides managers and engineers with a powerful tool for effectively capitalizing on the immense potential of today's advancing technology
Keywords: Technology inovation,Thay đổi công nghệ,Production,Sản xuất; Management,Quản lý,Management,Quản trị